2019
DOI: 10.3389/fmed.2019.00167
|View full text |Cite
|
Sign up to set email alerts
|

Itch Processing in the Skin

Abstract: Itching can result from activity of specialized primary afferent neurons (“pruriceptors”) that have been shown to express certain molecular markers such as B-type natriuretic peptide and several members of the Mrgpr-family in rodents. On the other hand, neurons involved in pain processing (“nociceptors”) can also provoke itching when the activation site is restricted to an isolated tiny spot within the epidermis. Individuals classified as having sensitive skin report increased itching and pain sensations upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 86 publications
0
34
0
2
Order By: Relevance
“…However, the MRGPRs can be activated by various endogenous and exogenous peptides or molecules, such as antimicrobial host defense or opioid peptides, SP or eosinophilic granules, but also by drugs like vancomycin or chloroquine (CQ) ( 12 , 207 ). Particularly, MRGPRA3 and MRGPRC11 in mice as well as the human ortholog MRGPRX1 got into the focus of pruritus researchers over the past decade ( 12 , 208 ). It was shown that CQ activated MRGPRA3 leading to a pruritus signal via the activation of TRPA1 ( 24 ).…”
Section: Receptors In Neuro-immune Interactionsmentioning
confidence: 99%
“…However, the MRGPRs can be activated by various endogenous and exogenous peptides or molecules, such as antimicrobial host defense or opioid peptides, SP or eosinophilic granules, but also by drugs like vancomycin or chloroquine (CQ) ( 12 , 207 ). Particularly, MRGPRA3 and MRGPRC11 in mice as well as the human ortholog MRGPRX1 got into the focus of pruritus researchers over the past decade ( 12 , 208 ). It was shown that CQ activated MRGPRA3 leading to a pruritus signal via the activation of TRPA1 ( 24 ).…”
Section: Receptors In Neuro-immune Interactionsmentioning
confidence: 99%
“…In the case of a pruriceptive itch, skin inflammation results in the recruitment and activation of immune cells to the skin epithelium. Activated immune cells release pro-inflammatory mediators, such as interleukin (IL) 31 and IL-33 that sensitize pruriceptors, leading to peripheral sensitization and activation of itch signaling pathways [121]. In the case of a neuropathic itch, peripheral nerve injury can cause inflammation of the nervous system, so called neuroinflammation.…”
Section: The Immune Mechanisms Of Prv-induced Neuropathic Itchmentioning
confidence: 99%
“…A particular attention should be given to γ‐aminobutyric acid (GABA) which in skin is produced by fibroblasts [ 88 ] and immune cells, [ 89 ] and released by interneurons involved itch transmission. [ 58 ] GABA exerts multiple local effects in skin, including fibroblasts proliferation and regulation of collagen I expression. [ 90,91 ] However, GABA is also known as a universal inter‐kingdom communication molecule.…”
Section: Bacterial Sensing Of Skin Neurohormones and Neurotransmittersmentioning
confidence: 99%
“…[ 57 ] More recently, the study of itch revealed that BNP present by skin primary sensory afferent fibres should be a key mediator in a specific itch neurotransmission pathway. [ 58 ] Natriuretic peptides, and especially CNP, are also produced locally by endothelial cells and ANP, synthesized by cardiomyocytes, is circulating in blood as an hormone. [ 56 ] In this regard, in skin the bulge of the hair follicle is a region of special interest because of the presence of a dense network of capillary vessels at the immediate vicinity of the hair follicle hollow [ 59 ] where gland ducts open to a rich microbial community.…”
Section: Bacterial Sensing Of Skin Neurohormones and Neurotransmittersmentioning
confidence: 99%